2006
DOI: 10.1207/s15548430jlr3801_1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Student Questioning and Prior Knowledge to Construction of Knowledge from Reading Information Text

Abstract: This study investigated the relationship of student-generated questions and prior knowledge with reading comprehension. A questioning hierarchy was developed to describe the extent to which student-generated questions seek different levels of conceptual understanding. Third-and fourth-grade students (N = 360) posed questions that were related to their prior knowledge and reading comprehension, measured as conceptual knowledge built from text. The results indicated that student questioning accounted for a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 23 publications
8
106
1
14
Order By: Relevance
“…Nevertheless, the increasing use of digital platforms and tools necessarily calls for a re-examination of the validity of teaching about critical thinking, investigation, and analysis through traditional models of paper writing and examinations where research material is largely re-presented in different ways. Recent investigations into youth and literacies in education have shown that proper pedagogical methods that approach critical inquiry online, knowledge construction, reliability and savvy web navigation can increase digital and media literacy (Kuiper & Volman, 2008;Sanchez et al, 2006;Taboada & Guthrie, 2006). While traditional techniques remain relevant for students today, there is a need to explore pedagogical models that aim to empower critical thinking within the context of digital realities for youth today.…”
Section: Why Curation?mentioning
confidence: 99%
“…Nevertheless, the increasing use of digital platforms and tools necessarily calls for a re-examination of the validity of teaching about critical thinking, investigation, and analysis through traditional models of paper writing and examinations where research material is largely re-presented in different ways. Recent investigations into youth and literacies in education have shown that proper pedagogical methods that approach critical inquiry online, knowledge construction, reliability and savvy web navigation can increase digital and media literacy (Kuiper & Volman, 2008;Sanchez et al, 2006;Taboada & Guthrie, 2006). While traditional techniques remain relevant for students today, there is a need to explore pedagogical models that aim to empower critical thinking within the context of digital realities for youth today.…”
Section: Why Curation?mentioning
confidence: 99%
“…To summarize a text, the reader has to select which parts are most important, condensing the material and replace higher-order concepts and integrate what you read in a coherent and accurate (Pressley & Schneider, 1997;Taboada & Guthrie, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To become active learners and independent thinkers, learners should generate questions that form, focus, and guide their thinking [17]. Several studies have found that metacognitive activities externally imposed, for example by teachers, generate questions that are less effective than those produced by students [7].…”
Section: Asking Questions As Metacognitive Skillsmentioning
confidence: 99%